2020
DOI: 10.3390/nu12102905
|View full text |Cite
|
Sign up to set email alerts
|

Food Addiction Is Associated with Binge Eating and Psychiatric Distress among Post-Operative Bariatric Surgery Patients and May Improve in Response to Cognitive Behavioural Therapy

Abstract: The current study examined clinical correlates of food addiction among post-operative bariatric surgery patients, compared the clinical characteristics of patients with versus without food addiction, and examined whether a brief telephone-based cognitive behavioural therapy (Tele-CBT) intervention improves food addiction symptomatology among those with food addiction. Participants (N = 100) completed measures of food addiction, binge eating, depression, and anxiety 1 year following bariatric surgery, were rand… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 59 publications
0
50
0
3
Order By: Relevance
“…Other initiatives can be applied in the context of FA, such as acceptance and commitment therapy (ACT) [ 148 ]. A wide range of motivational interviewing and cognitive behavioral therapies (CBT), which requires patients to critically evaluate the thoughts, feelings, and behaviors resulting in maladaptive responses and helps them to find their own solutions, adapted to their daily lives, can also be implemented in the context of FA and have already demonstrated their usefulness [ 149 ]. Such results must be replicated on larger cohorts and in the long term, and different types of CBT should be compared to provide recommendations about matching strategies to individual profiles, depending on their personality traits and susceptibilities, for example.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Other initiatives can be applied in the context of FA, such as acceptance and commitment therapy (ACT) [ 148 ]. A wide range of motivational interviewing and cognitive behavioral therapies (CBT), which requires patients to critically evaluate the thoughts, feelings, and behaviors resulting in maladaptive responses and helps them to find their own solutions, adapted to their daily lives, can also be implemented in the context of FA and have already demonstrated their usefulness [ 149 ]. Such results must be replicated on larger cohorts and in the long term, and different types of CBT should be compared to provide recommendations about matching strategies to individual profiles, depending on their personality traits and susceptibilities, for example.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Studies were conducted in Australia and New Zealand (n 5 4) [42][43][44][45], Canada (n 5 4) [46][47][48][49], Europe (n 5 3 studies, reported across 5 publications) [50][51][52][53][54], the United States (n 5 2 studies, reported across 3 publications) [55][56][57], and Korea (n 5 1) [58]. Among the studies, 10 were conducted as RCTs (reported across 13 publications) [43][44][45][46][47]49,[51][52][53][54][55][56][57], 3 were controlled before and after studies [42,48,50], and 1 was a quasi-experimental design [58]. The majority of the study settings were tertiary or public hospitals (n 5 8 studies, reported across 9 publications) [42][43][44][48][49][50]52,53,58].…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…Among the studies, 10 were conducted as RCTs (reported across 13 publications) [43][44][45][46][47]49,[51][52][53][54][55][56][57], 3 were controlled before and after studies [42,48,50], and 1 was a quasi-experimental design [58]. The majority of the study settings were tertiary or public hospitals (n 5 8 studies, reported across 9 publications) [42][43][44][48][49][50]52,53,58]. Two were conducted in a medical or local center (reported across 4 publications) [51,[54][55][56], 1 in a public health service [47], 1 study was not sitespecific and recruited via social media [45], and 2 studies did not report the setting [46,57].…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…This special issue presents a collection of articles, contributed by renowned experts, researchers, and clinicians spanning different disciplines, that adds to the knowledge on the clinical utility of food addiction and eating addiction. The articles in this collection include reviews [ 1 , 2 , 3 , 4 , 5 ] as well as original research utilizing a variety of methodologies and study designs such as clinical trials [ 6 , 7 , 8 ], cross-sectional studies [ 9 , 10 ], and surveys [ 11 ].…”
mentioning
confidence: 99%
“…A number of authors contributed papers to this special issue that emphasize the need for individual-level and societal-level interventions for food addiction. In a sample of post-operative bariatric surgery patients, Cassin et al [ 6 ] found that those with food addiction reported greater binge eating characteristics and psychiatric distress relative to those without, and there was preliminary evidence that a brief telephone-based cognitive behavioural therapy intervention may lead to short-term improvement in food addiction symptoms. Two other studies examined food addiction in the context of behavioural weight loss programs.…”
mentioning
confidence: 99%